P-P13 Long-term outcome after portal vein resection during pancreaticoduodenectomy for pancreatic ductal adenocarcinoma: a propensity score matched analysis. (16th December 2021) - Russell, James; Stevens, Claire; Bhome, Rahul; Karavias, Dimitrios; Arshad, Ali; Takhar, Arjun; Armstrong, Thomas; Primrose, John; Green, Brian; Hamady, Zaed
Abstract: Background: Portal vein resection (PVR) with pancreaticoduodenectomy (PD) is often performed to achieve clear margins for patients with vascular involvement in pancreatic ductal adenocarcinoma (PDAC). However, there is evidence to suggest that patients undergoing PVR often have more advanced cancers, therefore the impact of PVR on survival and recurrence remains unclear. The aim of this study is to assess overall (OS) and recurrence free (RFS) survival in patients who underwent PVR during PD, with particular attention to margin positivity. Methods: A retrospective analysis was performed on 638 patients who underwent PD during a 12-year period. Exclusion criteria included PD for non-PDAC tumours, neoadjuvant chemotherapy or intra-operative radiotherapy. 374 patients were included in the study (90 PVR and 284 non-PVR). Patient characteristics and histopathological factors associated with OS and RFS were then evaluated using univariate and multivariate Cox regression analyses. 270 patients (90 PVR and 180 non-PVR), were matched by propensity score based on perineural invasion, pT and pN staging. The Kaplan-Meier method was used to calculate survival and log-rank tests. Results: Resection margin positivity was associated with shorter OS and RFS (p < 0.0001), and the superior mesenteric vein (SMV) margin was the most significant risk factor for survival on competing risks analysis. Absent adjuvant chemotherapy, nodal metastasis and margin positivity were independent risk factors for OS and RFS on multivariate analysis. PVR was associated with higher intra-operative blood loss (p = 0.009), but was not associated with increased length of stay, complications or readmissions. PVR patients had increased pT staging, nodal metastasis and perineural invasion, however, there was no difference in OS (p = 0.551) or RFS (p = 0.256) between PVR and non-PVR after propensity matching. Conclusions: Positive resection margins are associated with shorter survival times, and the SMV margin is the most significant prognostic indicator for overall survival and recurrence compared to other margins. PVR is a relatively safe procedure, however, it does not achieve the intended survival benefits of complete margin clearance. The impact on survival for margin positivity, particularly the SMV margin, and nodal metastasis should be considered when making decisions with regards to vein resection and adjuvant treatments.